Evaluation of steroids for acute COVID in the prevention of long COVID in children: An EHR and pediatric cohort study from the RECOVER Initiative - Kathryn Hirabayashi; Vitaly Lorman; Shannon Wuller; Leyna V. Aragon; Ravi Jhaveri; Nita Jain; John Erik Leikauf; Jennifer A. Muszynski; Aaron Thomas Martinez; Miranda Higginbotham; Payal B. Patel; Marc A. Sala; et al. (PLoS ONE, 2026)
Background Studies have shown that use of immunomodulators during the acute phase of SARS-CoV-2 infection may decrease development of post-acute sequelae of SARS-CoV-2 (PASC) or long COVID; however, such studies have not been conducted in children. Objective Evaluate the effectiveness of steroid use during the acute phase of SARS-CoV-2 infection in preventing long COVID in children. Methods We conducted a retrospective cohort study using target trial emulation methodology to compare children and youth who did and did not receive dexamethasone, prednisone, prednisolone or methylprednisolone within 12 days of SARS-CoV-2 infection. Inverse propensity of treatment weighting was used to balance covariates between treated and untreated patients in hospitalized and outpatient groups. The primary outcome was the development of PASC in the 1–6 months following acute infection using a computable phenotype definition. Secondary outcomes included respiratory, musculoskeletal, gastrointestinal and neurological subphenotypes and the PASC ICD-10-CM diagnosis code. We calculated hazard ratios from Cox proportional models with 95% confidence intervals. Results From a starting cohort of 854,128 children/youth, of whom 768,845 (90.0%) were outpatients and 85,283 (10.0%) were inpatients at the time of SARS-CoV-2 infection, the weighted outpatient cohort included 22,085 steroid-treated children and 20,373 in the non-steroid group. Following weighting, the hospitalized cohort included 11,250 steroid-treated children and 10,340 untreated children. In hospitalized patients, there were no significant treatment differences in the development of PASC in the 1−6 months following acute SARS-CoV-2 infection except for a lower risk of gastrointestinal PASC in treated patients (HR: 0.58; [95% CI: 0.39–0.85], p = 0.01). In outpatients, no treatment differences were observed in the development of PASC subphenotypes. Conclusions Steroids administered during acute SARS-CoV-2 infection did not lead to a decreased risk of PASC, with the exception of gastrointestinal presentations. Additional studies are needed to confirm the benefit of steroids and other immunomodulators in preventing long COVID.